PROXIMAL PEDICLED V-Y ADVANCEMENT FLAP FOR CLOSURE OF SURGICAL DEFECT ON THE BACK OF THE HAND - Tavares, Ermelindo; Castellano, David Pacheco; Rosa, José (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Introduction: The V-Y advancement flap is widely used in the reconstruction of surgical defects of the face, particularly on the periocular or eyelid areas. Its use in other locations has been taking new indications with high reconstructive quality. Case report: An 86-year-old female patient underwent wide excision of squamous cell carcinoma of the back of the right hand. Proximal pedicled V-Y advancement flap emerging from the radial edge of the hand was used to close the surgical defect. There was no partial or total flap necrosis. The aesthetic result was quite acceptable. Conclusion: The V-Y advancement flap is a viable surgical alternative for reconstruction of surgical defects of the back of the hand. KEYWORDS – Hand; Squamous cell carcinoma; Reconstructive surgical procedures; Skin transplantation; Surgical flaps.